ANALISIS MODEL PEMBELAJARAN REACT BERBANTUAN APLIKASI GEOGEBRA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Ulina Agustina Harahap; Sri Rahmah Dewi Saragih (Smart Education, 2026)
Abstract: The aim of this research is to outline the implementation of the REACT method, supported by the Geogebra software, to improve critical thinking skills employing a qualitative approach. The information for this research was gathered from studies conducted with students at Yapim Simpang Kawat Private High School. The techniques for collecting data in this research included observations and interviews, interviews, assessments of critical thinking skills, and documentation. The techniques for data analysis encompass multiple steps, which include calculating the results of student tests and categorizing the level of critical thinking skills both on an individual basis and collectively for the class. The findings of this study indicate that among 36 students, 25 demonstrated critical thinking skills classified as